Composite coating and preparation method thereof
By depositing a composite coating formed by a single α, β, and γ plasma on the PCB, the lack of existing coating in high -frequency signal transmission and sour sweat protection is solved, and excellent sour sweat protection and high frequencies are achieved. Taking into account the efficiency of signal transmission.
Patent Information
- Application Number
- CN202310937077.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-01-28
AI Technical Summary
While protecting the PCB from moisture, salt spray and mold, the existing protective coatings are difficult to maintain the fidelity and transmission rate of high-frequency signals, and have poor protection against acid sweat, making it impossible to achieve long-term protection.
The plasma aggregate coating Ⅰ formed by a plasma formed by a monomer α and a single β, carbon silicon coating Ⅱ formed by the plasma formed by the plasma of monomer γ is formed to form a composite coating. This composite coating is deposited on the substrate through plasma discharge technology, has excellent sour sweat protection performance, and can maintain the conductivity by controlling the thickness of the coating.
The excellent protective performance of sour sweat is achieved, while maintaining the transmission efficiency and conductivity of high -frequency signals, avoiding the obstruction of the conductivity part, simplifying the process and reducing the cost.
Smart Images

Figure BDA0004365998290000021 
Figure BDA0004365998290000022 
Figure BDA0004365998290000023
Abstract
Description
Technical Field
[0001] The invention belongs to the field of plasma chemistry, and in particular relates to a plasma polymerization protective coating and a preparation method thereof. Background Art
[0002] For electronic devices, moisture is the most common and major factor that reduces their service life. Moisture intrusion can cause oxidation and corrosion of metals in integrated circuits. Metal corrosion in a humid environment is a common type of failure for integrated circuits. In addition, moisture-induced delamination and cracking of plastic packaging is another common cause of integrated circuit failure.
[0003] Protective coating is an important protective measure to protect PCB (printed circuit board assembly) from moisture, salt spray and mold. In order to improve the corrosion resistance of PCB, the thickness of surface protective coating is getting thicker and thicker. However, this conformal coating usually reduces the heat dissipation efficiency of electronic components, and even reduces the fidelity and transmission rate of high-frequency signals. The high-frequency signal transmission speed and signal fidelity of PCB are not only strongly dependent on the dielectric constant and dielectric loss of the coating, but also directly related to the thickness of the coating. Plasma enhanced chemical vapor deposition (PECVD) can be used to make a nano-film layer with good winding properties on the PCB. However, most of the coatings are salt-resistant coatings, which have poor protection against acid sweat and cannot achieve long-term protection. In addition, for example, for PCB boards or data cables, the protective coatings usually prepared will affect the electrical conductivity of the electrically conductive part of the substrate, that is, the protective coating needs to be deposited or prepared under the condition of shielding the electrically conductive part, so the process is relatively complicated. Summary of the invention
[0004] The specific embodiment of the present invention provides a composite coating with excellent acid sweat protection performance and a preparation method thereof, and the specific scheme is as follows:
[0005] A composite coating, the composite coating comprising coating I and coating II sequentially deposited on a substrate;
[0006] The coating I is a plasma polymerized coating formed by plasma of monomer α and monomer β;
[0007] The monomer α has a structure shown in formula (1-1),
[0008]
[0009] wherein Ar is a structure with an aromatic ring, T1 is -OC(O)- or -C(O)-O-, X1 is a connecting part, Y1 is a connecting part, R1, R2 and R3 are independently selected from hydrogen atoms, halogen atoms, C1-C 10 Alkyl or C1-C 10 The halogen atom replaces the alkyl group,
[0010] The monomer β has a structure shown in formula (2-1),
[0011]
[0012] Wherein, S contains one or more -OC(O)- or -C(O)-O-, and R4, R5, R6, R7, R8 and R9 are independently selected from hydrogen atoms, halogen atoms, C1-C 10 Alkyl or C1-C 10 The halogen atom replaces the alkyl group;
[0013] The coating II is a plasma polymerized coating formed by plasma of monomer γ.
[0014] The monomer γ is a siloxane having a structure represented by formula (3-1), formula (3-2) or formula (3-3),
[0015] Among them, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 18 and R 19 are independently selected from hydrogen atoms, C1-C 20 Hydrocarbon or C1-C 20 The alkoxy group, R 17 Selected from C1-C 20 Hydrocarbon, C0-C 20 A hydrocarbon silyl group, n is an integer of 1-100, m is an integer of 3-10, wherein R 10 , R 11 , R 12 and R 13 At least one of R is not a hydrogen atom, 14 , R 15 and R 16 At least one of R is not a hydrogen atom, 18 and R 19 At least one of them is not a hydrogen atom.
[0016] Optionally, R1, R2, R3, R4, R5, R6, R7, R8 and R9 are independently selected from a hydrogen atom or a methyl group.
[0017] Optionally, X1 is a structure shown in the following formula (1-2),
[0018]
[0019] Among them, X 11 is a connecting bond, -O- or -C(O)-, X 12 is the connecting key, C1-C 10 Alkylene or C1-C 10 The halogen atom replaces the alkylene group;
[0020] Y1 is a connecting bond, C1-C 10 Alkylene or C1-C 10 The halogen atom(s) of the alkylene group is substituted by the alkylene group.
[0021] Optionally, Ar is a benzene ring structure or a benzene ring structure with a substituent.
[0022] Optionally, the monomer α has a structure shown in formula (1-3),
[0023]
[0024] Wherein, T2 is -OC(O)- or -C(O)-O-, X2 is a connecting part, and Y2 is a connecting part; R 21 , R 22 and R 23 are independently selected from hydrogen atoms, halogen atoms, C1-C 10 Alkyl or C1-C 10 The halogen atom replaces the alkyl group.
[0025] Optionally, X2 is a structure shown in the following formula (1-4),
[0026] *-X 22 -X 21 -*
[0027] (1-4)
[0028] Among them, X 21 is a connecting bond, -O- or -C(O)-, X 22 is the connecting key, C1-C 10 Alkylene or C1-C 10 The halogen atom replaces the alkylene group;
[0029] Y2 is a connecting bond, C1-C 10 Alkylene or C1-C 10 The halogen atom(s) of the alkylene group is substituted by the alkylene group.
[0030] Optionally, the R 21 , R 22 and R 23 are independently selected from a hydrogen atom or a methyl group.
[0031] Optionally, the monomer α is selected from at least one of 2-phenoxyethyl acrylate, phenyl acrylate, diallyl terephthalate or phenyl methacrylate.
[0032] Optionally, the S contains two -OC(O)- or -C(O)-O-.
[0033] Optionally, the S has a structure shown in formula (2-2),
[0034]
[0035] Among them, R 24 C2-C 10 Alkylene or C2-C 10 The halogen atom-substituted alkylene group is substituted with y, and y is an integer from 0 to 10.
[0036] Optionally, the monomer β is selected from at least one of 2-methyl-2-acrylate-1,9-nonanediol ester, 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol dimethacrylate, methacrylic anhydride, dipropylene-2-enyl-2-methylenesuccinate, dipropylene-2-enyl 2-benzylidenemalonate or diethyl diallylmalonate.
[0037] Optionally, the R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 18 and R 19 are independently selected from hydrogen, methyl or ethyl, R 17 Selected from methyl, ethyl, silyl, methylsilyl, dimethylsilyl or trimethylsilyl.
[0038] Optionally, the monomer γ is selected from one or more of octamethylcyclotetrasiloxane, octamethyltrisiloxane, hexamethylcyclotrisiloxane, trimethylcyclotrisiloxane, tetramethyltetravinylcyclotetrasiloxane, dodecamethylcyclohexasiloxane, decamethylcyclopentasiloxane, decamethyltetrasiloxane, dimethylsiloxane, tetraethoxysilane, tetramethoxysilane, allyltrimethoxysilane, hexamethyldisiloxane, tetramethyldisiloxane, hexaethyldisiloxane, diphenyldimethoxysilane, diphenyldiethoxysilane and phenyltris(trimethylsiloxy)silane.
[0039] Optionally, the substrate is metal, plastic, fabric, glass, electrical component, optical instrument or electrical part.
[0040] Optionally, the substrate is a PCB board or a data cable.
[0041] Optionally, the thickness of coating I is 100-310 nm, the thickness of coating II is 10-50 nm, and the thickness of the composite coating is 150-330 nm.
[0042] Optionally, the coating may be electrically conductive.
[0043] Optionally, the coating is immersed in artificial sweat with a pH of 4.7, a voltage of 3.7 V is applied, and the circuit current is monitored within 30 minutes, and the current change is no greater than 0.6 mA.
[0044] A method for preparing the composite coating as described above comprises:
[0045] Providing a substrate, placing the substrate in a plasma reaction chamber, evacuating the chamber to 10-200 mTorr, and introducing an inert gas such as He, Ar, O2 or a mixed gas thereof;
[0046] The vapor of monomer α and monomer β is introduced into the reaction chamber, and plasma discharge is started to form a plasma polymerization coating I;
[0047] The steam of monomer γ is introduced into the reaction chamber, and plasma discharge is started to form a plasma polymerized coating II on the surface of the coating I.
[0048] Optionally, the thickness of coating I and / or coating II is adjusted to ensure that the coating has acid sweat protection and electrical conductivity.
[0049] A device, at least part of the surface of the device having a protective coating comprising any of the above.
[0050] The composite coating of the specific implementation scheme of the present invention forms coating I with the plasma of unsaturated ester monomers and ester coupling agent monomers having aromatic rings, and then forms carbon silicon coating II on coating I with the plasma of siloxane monomers. The composite coating has excellent acid sweat protection performance, and further, by controlling the thickness of the coating, the coating can have excellent acid sweat protection performance and excellent electrical conductivity performance. For products with electrical conductivity requirements, such as PCB boards or data cables, there is no need to mask the electrically conductive parts or subsequently remove the composite coating of the electrically conductive parts, thereby reducing the process and saving costs. DETAILED DESCRIPTION
[0051] A specific embodiment of the present invention provides a composite coating, the composite coating comprising coating I and coating II sequentially deposited on a substrate;
[0052] The coating I is a plasma polymerized coating formed by plasma of monomer α and monomer β;
[0053] The monomer α has a structure shown in formula (1-1),
[0054]
[0055] wherein Ar is a structure with an aromatic ring, T1 is -OC(O)- or -C(O)-O-, X1 is a connecting part, Y1 is a connecting part, R1, R2 and R3 are independently selected from hydrogen atoms, halogen atoms, C1-C 10 Alkyl or C1-C 10 The halogen atom replaces the alkyl group,
[0056] The monomer β has a structure shown in formula (2-1),
[0057]
[0058] Wherein, S contains one or more -OC(O)- or -C(O)-O-, and R4, R5, R6, R7, R8 and R9 are independently selected from hydrogen atoms, halogen atoms, C1-C 10 Alkyl or C1-C 10 The halogen atom replaces the alkyl group;
[0059] The coating II is a plasma polymerized coating formed by plasma of monomer γ.
[0060] The monomer γ is a siloxane having a structure represented by formula (3-1), formula (3-2) or formula (3-3),
[0061]
[0062] Among them, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 18 and R 19 are independently selected from hydrogen atoms, C1-C 20 Hydrocarbon or C1-C 20 The alkoxy group, R 17 Selected from C1-C 20 Hydrocarbon, C0-C 20 A hydrocarbon silyl group, n is an integer of 1-100, m is an integer of 3-10, wherein R 10 , R 11 , R12 and R 13 At least one of R is not a hydrogen atom, 14 , R 15 and R 16 At least one of R is not a hydrogen atom, 18 and R 19 At least one of them is not a hydrogen atom.
[0063] In the composite coating of the specific embodiment of the present invention, in some specific embodiments, Ar is a benzene ring or a heteroaromatic ring with a substituent on the aromatic ring, and in other specific embodiments, Ar is a benzene ring or a heteroaromatic ring without a substituent on the aromatic ring.
[0064] In the composite coating of a specific embodiment of the present invention, X1 and Y1 are connecting parts, X1 is used to connect the structure Ar with an aromatic ring and the ester bond T1, and Y1 is used to connect the ester bond T1 and the saturated carbon-carbon double bond. In some specific embodiments, X1 is a structure shown in the following formula (1-2):
[0065] *-X 11 -X 12 -*
[0066] (1-2)
[0067] Among them, X 11 is a connecting bond, -O- or -C(O)-, X 12 is the connecting key, C1-C 10 Alkylene or C1-C 10 The halogen atom replaces the alkylene group; the Y1 is a connecting bond, C1-C 10 Alkylene or C1-C 10 The alkylene group includes a straight chain alkylene group, such as methylene, ethylene, propylene or butylene, or a branched alkylene group, such as isopropylene or isobutylene.
[0068] In some embodiments of the composite coating of the present invention, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 14 , R 15 and R 16 are independently selected from a hydrogen atom or a methyl group.
[0069] In some embodiments of the composite coating of the present invention, the monomer α has a structure shown in formula (1-3),
[0070]
[0071] Wherein, T2 is -OC(O)- or -C(O)-O-, X2 is a connecting part for connecting the benzene ring and the ester bond T2, and Y2 is a connecting part for connecting the ester bond T2 and the carbon-carbon double bond;
[0072] R 21 , R 22 and R 23 are independently selected from hydrogen atoms, halogen atoms, C1-C 10 Alkyl or C1-C 10 The alkyl group includes a straight chain alkyl group, such as methyl, ethyl, propyl or butyl, or a branched alkyl group, such as isopropyl or isobutyl.
[0073] In some specific embodiments of the composite coating of the present invention, in the structure shown in formula (1-3), the two substituents on the benzene ring are para-substituted, and in other embodiments they can also be ortho-substituted or meta-substituted.
[0074] In some specific embodiments of the composite coating of the present invention, X2 is a structure shown in the following formula (1-4):
[0075] *-X 22 -X 21 -*
[0076] (1-4)
[0077] Among them, X 21 is a connecting bond, -O- or -C(O)-, X 22 is the connecting key, C1-C 10 Alkylene or C1-C 10 The halogen atom replaces the alkylene group; the Y2 is a connecting bond, C1-C 10 Alkylene or C1-C 10 The alkylene group includes a straight chain alkylene group, such as methylene, ethylene, propylene or butylene, or a branched alkylene group, such as isopropylene or isobutylene.
[0078] In some embodiments of the composite coating of the present invention, the R 21 , R 22 and R 23 are independently selected from a hydrogen atom or a methyl group.
[0079] In the composite coating of a specific embodiment of the present invention, as a specific non-limiting example, the monomer α is selected from at least one of 2-phenoxyethyl acrylate (CAS No.: 48145-04-6), phenyl acrylate (CAS No.: 937-41-7), diallyl terephthalate (CAS No.: 1026-92-2) or phenyl methacrylate (CAS No.: 2177-70-0).
[0080] In some specific embodiments of the composite coating of the specific embodiments of the present invention, the S contains two -OC(O)- or -C(O)-O-, that is, S contains two -OC(O)-, two -C(O)-O- or one -OC(O)- or -C(O)-O-.
[0081] In some embodiments of the composite coating of the present invention, S has a structure shown in formula (2-2),
[0082]
[0083] Among them, R 24 C2-C 10 Alkylene or C2-C 10 wherein y is an integer from 0 to 10, and specifically 0, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.
[0084] The composite coating of the specific embodiment of the present invention, as a specific non-limiting example, the monomer β is selected from 2-methyl-2-acrylate-1,9-nonanediol ester (CAS No.: 65833-30-9), 1,4-butanediol dimethacrylate (CAS No.: 2082-81-7), 1,6-hexanediol dimethacrylate (CAS No.: 6606-59-3), ethylene glycol dimethacrylate (CAS No.: 97-90-5), diethylene glycol dimethacrylate (CAS No.: 2358-84-1), triethylene glycol dimethacrylate (CAS No.: ... At least one of tetraethylene glycol dimethacrylate (CAS No.: 109-16-0), tetraethylene glycol dimethacrylate (CAS No.: 109-17-1), 1,3-butylene glycol dimethacrylate (CAS No.: 1189-08-8), neopentyl glycol dimethacrylate (CAS No.: 1985-51-9), methacrylic anhydride (CAS No.: 760-93-0), dipropylene-2-enyl-2-methylenesuccinate, dipropylene-2-enyl 2-benzylidenemalonate (CAS No.: 52505-39-2) or diethyl diallylmalonate (CAS No.: 3195-24-2).
[0085] In the composite coating of the specific embodiment of the present invention, in some specific embodiments, the hydrocarbon group can be an alkane group, an alkene group, an alkyne group or an aromatic hydrocarbon group. In some specific embodiments, the hydrocarbonoxy group can be an alkaneoxy group, an alkeneoxy group, an alkyneoxy group or an aromatic hydrocarbon group.
[0086] In the composite coating of the specific embodiment of the present invention, the hydrocarbon group includes a straight chain or branched hydrocarbon group, and the hydrocarbonoxy group includes a straight chain or branched hydrocarbonoxy group.
[0087] In some embodiments of the composite coating of the present invention, the R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 18 and R 19 are independently selected from hydrogen atoms, C1-C 10 Alkyl or C1-C 10 The alkoxy group, R 17 Selected from C1-C 10 Alkyl or C1-C 10 In some embodiments, the alkylsilyl group of R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 18 and R 19 are independently selected from C1-C4 alkyl or C1-C4 alkoxy, wherein R 17 is selected from C1-C4 alkyl or C1-C4 alkylsilyl. In some embodiments, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 18 and R 19 are independently selected from hydrogen, methyl or ethyl, R 17 Selected from methyl, ethyl, silicon (-SiH3), methylsilyl, dimethylsilyl or trimethylsilyl.
[0088] In some specific embodiments of the composite coating of the present invention, n and m are integers from 1 to 10, specifically 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.
[0089] In some embodiments of the composite coating of the specific embodiment of the present invention, the monomer γ is selected from octamethylcyclotetrasiloxane (CAS No.: 556-67-2), octamethyltrisiloxane (CAS No.: 107-51-7), hexamethylcyclotrisiloxane (CAS No.: 541-05-9), trimethylcyclotrisiloxane (CAS No.: 13269-39-1), tetramethyltetravinylcyclotetrasiloxane (CAS No.: 2554-06-5), dodecamethylcyclohexasiloxane (CAS No.: 540-97-6), decamethylcyclopentasiloxane (CAS No.: 541-02-6), decamethyltetrasiloxane (CAS No.: 141-62-8), dimethyl ... One or more of the following: tetraethoxysilane (CAS No.: 78-10-4), tetramethoxysilane (CAS No.: 681-84-5), allyltrimethoxysilane (CAS No.: 2551-83-9), hexamethyldisiloxane (CAS No.: 107-46-0), tetramethyldisiloxane (CAS No.: 3277-26-7), hexaethyldisiloxane (CAS No.: 994-49-0), diphenyldimethoxysilane (CAS No.: 6843-66-9), diphenyldiethoxysilane (CAS No.: 2553-19-7) and phenyltris(trimethylsiloxy)silane (CAS No.: 2116-84-9).
[0090] The composite coating of the specific embodiment of the present invention can adjust the ratio of monomer α and monomer β according to the specific monomer situation. In some specific embodiments, the molar ratio of monomer α and monomer β is between 1:6 and 6:1, for example, it can be 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1 or 6:1, etc.
[0091] In some embodiments of the composite coating of the specific embodiment of the present invention, the coating is immersed in artificial sweat with a pH of 4.7, a voltage of 3.7V is applied, and the circuit current is monitored within 30 minutes, and the current change is no more than 0.6mA.
[0092] The composite coating of the specific embodiment of the present invention, in some specific embodiments, the substrate is various plastics, fabrics, glass, electrical components or optical instruments, etc. Specifically, the electrical component can be a printed circuit board (PCB), an electronic product or an electronic assembly semi-finished product, etc. When the substrate is an electronic product, examples are given but not limited to mobile phones, tablet computers, keyboards, e-readers, wearable devices, displays, headphones, etc. The substrate can also be any suitable electrical component of the electrical component, specifically, the electrical component can be a data line (such as Type-C data line, USB data line, Lighting data line, etc.), a sensor, a resistor, a capacitor, a transistor, a diode, an amplifier, a relay, a transformer, a battery, a fuse, an integrated circuit, a switch, an LED, an LED display, a piezoelectric element, an optoelectronic component or an antenna or an oscillator, etc. In some specific embodiments, the coating can be electrically conductive, and the substrate is a product with electrical conductivity requirements, such as a PCB board or a data line. The product with the coating has excellent protection performance and maintains good electrical conductivity.
[0093] In the composite coating of the specific embodiment of the present invention, in some specific embodiments, the thickness of the coating I is 100-310nm, and specific examples include 100nm, 120nm, 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm or 310nm, etc., the thickness of the coating II is 10-50nm, and specific examples include 10nm, 20nm, 30nm, 40nm or 50nm, etc., and the thickness of the composite coating is 150-330nm, and specific examples include 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm, 320nm or 330nm, etc. By controlling the coating thickness within the thickness range, it can be ensured that the coating has excellent protective properties and maintains good electrical conductivity, which can be adjusted according to specific monomer and product requirements.
[0094] The specific embodiment of the present invention also provides a method for preparing the above composite coating, comprising:
[0095] Providing a substrate, placing the substrate in a plasma reaction chamber, evacuating the chamber to 10-200 mTorr, and introducing an inert gas such as He, Ar, O2 or a mixed gas thereof;
[0096] The vapor of monomer α and monomer β is introduced into the reaction chamber, and plasma discharge is started to form a plasma polymerization coating I;
[0097] The steam of monomer γ is introduced into the reaction chamber, and plasma discharge is started to form a plasma polymerized coating II on the surface of the coating I.
[0098] In the composite coating preparation method according to the specific embodiment of the present invention, the monomer α, monomer β, monomer γ, coating I, coating II and substrate are described as above.
[0099] In the method for preparing the composite coating of the specific embodiment of the present invention, in some specific embodiments, the thickness of coating I and / or coating II is adjusted to ensure that the coating has acid sweat protection and electrical conductivity. Specifically, for example, the thickness of coating I and / or coating II can be adjusted by adjusting the plasma discharge time.
[0100] The preparation method of the composite coating of the specific embodiment of the present invention is to further enhance the bonding force between the plasma coating and the substrate. In some specific embodiments, the substrate is pretreated with plasma before coating, or the coating I is pretreated before coating the coating II. The specific pretreatment method is, for example, continuous discharge pretreatment under an inert gas or monomer atmosphere, with a discharge power of 100 to 600 W and a discharge time of 60 to 600 s, or pulse discharge pretreatment, with a pulse duty cycle of 0.1 to 70%, a pulse frequency of 10 to 500 Hz, a discharge power of 10 to 500 W, and a discharge time of 60 to 600 s. In other specific embodiments, the substrate is pretreated with heat, oxygen or high-energy radiation before coating.
[0101] The preparation method of the composite coating of the specific embodiment of the present invention, in some specific embodiments, in coating I or coating II, the plasma specific coating mode is continuous plasma discharge, the discharge power is 10 to 300 W, for example, it can be 10W, 50W, 100W, 150w, 200w, 250w or 300w, and the discharge time is 60 to 600s, for example, it can be 60s, 100s, 200s, 300s, 400s, 500s or 600s, etc. In some specific embodiments, in coating I or coating II, the plasma specific coating method is pulsed plasma discharge, wherein the pulse power is 10W-500W, and specifically, for example, it can be 10W, 50W, 100W, 150w, 200w, 250w, 300w, 350w, 400w, 450w or 500w, etc.; the pulse frequency is 10Hz-500Hz, and specifically, for example, it can be 10Hz, 15Hz, 20Hz, 25Hz, 30Hz, 35Hz, 40Hz, 45Hz, 50Hz, 1 00Hz, 200Hz, 300Hz, 400Hz or 500Hz, etc.; the pulse duty cycle is 0.1% to 70%, for example, it can be 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, etc.; the plasma discharge time is 600s-6000s, for example, it can be 600s, 1000s, 2000s, 3600s, 4000s, 5000s or 6000s, etc.
[0102] The preparation method of the composite coating of the specific embodiment of the present invention, in some specific embodiments, the flow rate of the monomer α, monomer β and monomer γ is 10-2400μL / min, for example, it can be 10μL / min, 50μL / min, 100μL / min, 200μL / min, 300μL / min, 500μL / min, 1000μL / min, 1500μL / min, 2000μL / min or 2400μL / min, etc.; the temperature in the cavity is controlled at 20℃-80℃, for example, it can be 20℃, 30℃, 40℃, 50℃, 60℃, 70℃ or 80℃, etc.; the monomer vaporization temperature is 50℃-120℃, for example, it can be 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃ or 120℃, etc., and vaporization occurs under vacuum conditions.
[0103] In the method for preparing the composite coating of the specific embodiment of the present invention, in some specific embodiments, the plasma discharge mode can be various existing discharge modes, for example, electrodeless discharge (such as radio frequency inductively coupled discharge, microwave discharge), single electrode discharge (such as corona discharge, plasma jet formed by monopole discharge), double electrode discharge (such as dielectric barrier discharge, bare electrode radio frequency glow discharge) and multi-electrode discharge (such as discharge using a floating electrode as the third electrode).
[0104] A specific embodiment of the present invention further provides a device, wherein at least a portion of the surface of the device has any of the above-mentioned composite coatings. In some specific embodiments, a portion of the surface or the entire surface of the device is only coated with the above-mentioned composite coating.
[0105] The present invention is further described below by means of specific examples.
[0106] Example
[0107] Test Method Description
[0108] Coating thickness test: The coating is applied on silicon wafers and tested using the American Filmetrics F20-UV-film thickness measuring instrument.
[0109] Acid sweat protection test: The pH value of acid sweat is 4.7, and the power-on voltage is 3.7V. The power-on test is to immerse the coated PCB board in artificial sweat, apply a voltage of 3.7V, and monitor the circuit current within 30 minutes. If the current change is greater than 0.6mA, it is judged as a failure.
[0110] Hydrophobic angle test: Tested by coating on silicon wafer according to GB / T 30447-2013 standard.
[0111] Data line transmission condition test: Use the data line to be coated in the same furnace, and judge the data line transmission condition by charging and data transmission. The data line transmission test is to use the lighting data line to be coated, connect the computer and the mobile phone respectively, if the data can be transmitted normally, it is judged that the data can be transmitted normally.
[0112] Example 1
[0113] The silicon wafer, data line and printed circuit board (PCB) were placed in a plasma chamber, the chamber was evacuated to 80 mTorr, helium was introduced with a flow rate of 40 sccm, and the chamber temperature was 50°C.
[0114] Phenyl acrylate and 1,4-butanediol dimethacrylate monomers are introduced into the chamber in a mass ratio of 1:4 after being vaporized at a vaporization temperature of 150°C, and plasma continuous discharge is turned on for pretreatment. The discharge power in the pretreatment stage is 180W, and the discharge lasts for 300s. Then pulse discharge is performed, with a pulse duty cycle of 35%, a pulse frequency of 250Hz, a pulse discharge power of 38W, a monomer flow rate of 480μL / min, and a reaction time of 2200s to form coating I.
[0115] Decamethyltetrasiloxane monomer vapor is introduced into the chamber after being vaporized at a vaporization temperature of 130°C. First, plasma continuous discharge is started to pretreat coating I. The discharge power in the pretreatment stage is 300W, and the discharge is continued for 300s. Then pulse discharge is performed, with a pulse duty cycle of 90%, a pulse frequency of 250Hz, a pulse discharge power of 250W, a monomer flow rate of 240μL / min, and a reaction time of 2400s to form coating II.
[0116] The thickness and hydrophobic angle of coating I and coating II were tested on silicon wafers, the acid sweat protection test was conducted on the PCB board coating, and the data line transmission condition was tested on the data line. The results are listed in Table 1 below.
[0117] Example 2
[0118] The silicon wafer, data line and printed circuit board (PCB) were placed in a plasma chamber, the chamber was evacuated to 80 mTorr, helium was introduced with a flow rate of 40 sccm, and the chamber temperature was 50°C.
[0119] 2-Phenoxyethyl acrylate and 2-methyl-2-acrylate-1,9-nonanediol ester monomers are introduced into the chamber in a mass ratio of 1:4 after being vaporized at a vaporization temperature of 150°C, and plasma continuous discharge is turned on for pretreatment. The discharge power in the pretreatment stage is 180W, and the discharge lasts for 300s. Then, pulse discharge is performed, wherein the pulse duty cycle is 35%, the pulse frequency is 250Hz, the pulse discharge power is 38W, the monomer flow rate is 480μL / min, and the reaction time is 3000s to form coating I.
[0120] Octamethylcyclotetrasiloxane monomer vapor is introduced into the chamber after being vaporized at a vaporization temperature of 130°C, and continuous plasma discharge is started to pretreat coating I. The discharge power in the pretreatment stage is 300W, and the discharge is continued for 300s. Subsequently, pulse discharge is performed, wherein the pulse duty cycle is 90%, the pulse frequency is 250Hz, the pulse discharge power is 250W, the monomer flow rate is 240μL / min, and the reaction time is 2400s to form coating II.
[0121] The thickness and hydrophobic angle of coating I and coating II were tested on silicon wafers, the acid sweat protection test was conducted on the PCB board coating, and the data line transmission condition was tested on the data line. The results are listed in Table 1 below.
[0122] Example 3
[0123] The silicon wafer, data line and printed circuit board (PCB) were placed in a plasma chamber, the chamber was evacuated to 80 mTorr, helium was introduced with a flow rate of 40 sccm, and the chamber temperature was 50°C.
[0124] 2-Phenoxyethyl acrylate and 2-methyl-2-acrylate-1,9-nonanediol ester monomers are introduced into the chamber in a mass ratio of 1:4 after being vaporized at a vaporization temperature of 150°C, and plasma continuous discharge is turned on for pretreatment. The discharge power in the pretreatment stage is 180W, and the discharge lasts for 300s. Then, pulse discharge is performed, wherein the pulse duty cycle is 35%, the pulse frequency is 250Hz, the pulse discharge power is 38W, the monomer flow rate is 480μL / min, and the reaction time is 5000s to form coating I.
[0125] Octamethylcyclotetrasiloxane monomer vapor is introduced into the chamber after being vaporized at a vaporization temperature of 130°C, and continuous plasma discharge is started to pretreat coating I. The discharge power in the pretreatment stage is 300W, and the discharge is continued for 300s. Subsequently, pulse discharge is performed, wherein the pulse duty cycle is 90%, the pulse frequency is 250Hz, the pulse discharge power is 250W, the monomer flow rate is 240μL / min, and the reaction time is 2400s to form coating II.
[0126] The thickness and hydrophobic angle of coating I and coating II were tested on silicon wafers, the acid sweat protection test was conducted on the PCB board coating, and the data line transmission condition was tested on the data line. The results are listed in Table 1 below.
[0127] Example 4
[0128] The silicon wafer, data line and printed circuit board (PCB) were placed in a plasma chamber, the chamber was evacuated to 80 mTorr, helium was introduced with a flow rate of 40 sccm, and the chamber temperature was 50°C.
[0129] 2-Phenoxyethyl acrylate and 2-methyl-2-acrylate-1,9-nonanediol ester were introduced into the chamber after being vaporized at a vaporization temperature of 150°C in a mass ratio of 1:4, and plasma continuous discharge was started for pretreatment. The discharge power in the pretreatment stage was 180W and the discharge lasted for 300s. Subsequently, pulse discharge was performed, wherein the pulse duty cycle was 35%, the pulse frequency was 250Hz, the pulse discharge power was 38W, the monomer flow rate was 480μL / min, and the reaction time was 1000s to form coating I.
[0130] Octamethylcyclotetrasiloxane monomer vapor is introduced into the chamber after being vaporized at a vaporization temperature of 130°C, and continuous plasma discharge is started to pretreat coating I. The discharge power in the pretreatment stage is 300W, and the discharge is continued for 300s. Subsequently, pulse discharge is performed, wherein the pulse duty cycle is 90%, the pulse frequency is 250Hz, the pulse discharge power is 250W, the monomer flow rate is 240μL / min, and the reaction time is 2400s to form coating II.
[0131] The thickness and hydrophobic angle of coating I and coating II were tested on silicon wafers, the acid sweat protection test was conducted on the PCB board coating, and the data line transmission condition was tested on the data line. The results are listed in Table 1 below.
[0132] Example 5
[0133] The silicon wafer, data line and printed circuit board (PCB) were placed in a plasma chamber, the chamber was evacuated to 80 mTorr, helium was introduced with a flow rate of 40 sccm, and the chamber temperature was 50°C.
[0134] 2-Phenoxyethyl acrylate and 2-methyl-2-acrylate-1,9-nonanediol ester were introduced into the chamber after being vaporized at a vaporization temperature of 150°C in a mass ratio of 1:4, and plasma continuous discharge was started for pretreatment. The discharge power in the pretreatment stage was 180W, and the discharge lasted for 300s. Then pulse discharge was performed, in which the pulse duty cycle was 35%, the pulse frequency was 250Hz, the pulse discharge power was 38W, the monomer flow rate was 480μL / min, and the reaction time was 6000s to form coating I.
[0135] Octamethylcyclotetrasiloxane monomer vapor is introduced into the chamber after being vaporized at a vaporization temperature of 130°C, and continuous plasma discharge is started to pretreat coating I. The discharge power in the pretreatment stage is 300W, and the discharge is continued for 300s. Subsequently, pulse discharge is performed, wherein the pulse duty cycle is 90%, the pulse frequency is 250Hz, the pulse discharge power is 250W, the monomer flow rate is 240μL / min, and the reaction time is 2400s to form coating II.
[0136] The thickness and hydrophobic angle of coating I and coating II were tested on silicon wafers, the acid sweat protection test was conducted on the PCB board coating, and the data line transmission condition was tested on the data line. The results are listed in Table 1 below.
[0137] Comparative Example 1
[0138] The silicon wafer, data line and printed circuit board (PCB) were placed in a plasma chamber, the chamber was evacuated to 80 mTorr, helium was introduced with a flow rate of 40 sccm, and the chamber temperature was 50°C.
[0139] 2-Phenoxyethyl acrylate and 2-methyl-2-acrylate-1,9-nonanediol ester were vaporized at a mass ratio of 1:4 at a vaporization temperature of 150°C and then introduced into the chamber. Plasma continuous discharge was started for pretreatment. The discharge power in the pretreatment stage was 180W, and the discharge lasted for 300s. Then pulse discharge was performed, with a pulse duty cycle of 35%, a pulse frequency of 250Hz, a pulse discharge power of 38W, a monomer flow rate of 480μL / min, and a reaction time of 3000s to form coating I.
[0140] Trimethoxy (1H, 1H.2H, 2H-tridecafluorooctyl) silane monomer vapor was introduced into the chamber after being vaporized at a vaporization temperature of 130°C, and plasma continuous discharge was started for pretreatment. The discharge power in the pretreatment stage was 300W, and the discharge lasted for 300s. Then pulse discharge was performed, with a pulse duty cycle of 90%, a pulse frequency of 250Hz, a pulse discharge power of 250W, a monomer flow rate of 240μL / min, and a reaction time of 2400s to form coating II.
[0141] The thickness and hydrophobic angle of coating I and coating II were tested on silicon wafers, the acid sweat protection test was conducted on the PCB board coating, and the data line transmission condition was tested on the data line. The results are listed in Table 1 below.
[0142] Comparative Example 2
[0143] The silicon wafer, data line and printed circuit board (PCB) were placed in a plasma chamber, the chamber was evacuated to 80 mTorr, helium was introduced with a flow rate of 40 sccm, and the chamber temperature was 50°C.
[0144] 2-Phenoxyethyl acrylate and 2-methyl-2-acrylate-1,9-nonanediol ester were vaporized at a mass ratio of 1:4 at a vaporization temperature of 150°C and then introduced into the chamber. Plasma continuous discharge was started for pretreatment. The discharge power in the pretreatment stage was 180W, and the discharge lasted for 300s. Then pulse discharge was performed, with a pulse duty cycle of 35%, a pulse frequency of 250Hz, a pulse discharge power of 38W, a monomer flow rate of 480μL / min, and a reaction time of 3000s to form coating I.
[0145] The thickness and hydrophobic angle of coating I were tested on silicon wafers, the acid sweat protection test was conducted on PCB board coatings, and the data line transmission condition was tested on data lines. The results are listed in Table 1 below.
[0146] Comparative Example 3
[0147] The silicon wafer, data line and printed circuit board (PCB) were placed in a plasma chamber, the chamber was evacuated to 80 mTorr, helium was introduced with a flow rate of 40 sccm, and the chamber temperature was 50°C.
[0148] Octamethylcyclotetrasiloxane monomer vapor is introduced into the chamber after being vaporized at a vaporization temperature of 130°C, and plasma continuous discharge is started for pretreatment. The discharge power in the pretreatment stage is 300W, and the discharge is continued for 300s. Then pulse discharge is performed, wherein the pulse duty cycle is 90%, the pulse frequency is 250Hz, the pulse discharge power is 250W, the monomer flow rate is 240μL / min, and the reaction time is 2400s to form a coating.
[0149] The thickness and hydrophobic angle of the coating were tested on silicon wafers, the acid sweat protection test was conducted on the PCB board coating, and the data line transmission condition was tested on the data line. The results are listed in Table 1 below.
[0150] Comparative Example 4
[0151] The silicon wafer, data line and printed circuit board (PCB) were placed in a plasma chamber, the chamber was evacuated to 80 mTorr, helium was introduced with a flow rate of 40 sccm, and the chamber temperature was 50°C.
[0152] Octamethylcyclotetrasiloxane monomer vapor is introduced into the chamber after being vaporized at a vaporization temperature of 130°C, and plasma continuous discharge is started for pretreatment. The discharge power in the pretreatment stage is 300W, and the discharge is continued for 300s. Then pulse discharge is performed, wherein the pulse duty cycle is 90%, the pulse frequency is 250Hz, the pulse discharge power is 250W, the monomer flow rate is 240μL / min, and the reaction time is 24000s to form a coating.
[0153] The thickness and hydrophobic angle of the coating were tested on silicon wafers, the acid sweat protection test was conducted on the PCB board coating, and the data line transmission condition was tested on the data line. The results are listed in Table 1 below.
[0154] Table 1 Test results of Examples 1-5 and Comparative Examples 1-4
[0155]
[0156] According to the results in Table 1 above, in Comparative Example 2, only a single-layer coating of coating I formed by the plasma of unsaturated ester monomers and ester coupling agent monomers with aromatic rings is formed, and in Comparative Examples 3 to 4, only a single-layer coating of carbon-silicon coating formed by the plasma of siloxane monomers is formed, and the single-layer coatings all have an acid sweat conduction time of less than 10 minutes. In Comparative Example 1, a composite coating consisting of coating I formed by the plasma of unsaturated ester monomers and ester coupling agent monomers with aromatic rings and coating II formed by the plasma of fluorine-containing siloxane is formed. It may be because fluorine in coating II is easy to aggregate on the surface, resulting in a loose surface that cannot reach complete coverage of the surface. Its composite coating also has an acid sweat conduction time of less than 10 minutes. The composite coatings of Examples 1 to 5, which are formed by the plasma of unsaturated ester monomers and ester coupling agent monomers with aromatic rings and the plasma of carbon-silicon coating II formed by the plasma of siloxane monomers, all have an acid sweat conduction time of more than 30 minutes, indicating that they have better acid sweat protection performance. According to the test results of data line transmission, Examples 1 to 4 have better data transmission effects than Example 5 by controlling the thickness of coating I, indicating that by controlling the thickness of coating I, coating II and the composite coating, for example, in Examples 1 to 4, coating I is controlled to be above 100nm and below 310nm, coating II is controlled to be above 10nm and below 50nm, and the thickness of the composite coating is controlled to be above 150nm and below 330nm, the entire composite coating has excellent acid and sweat protection performance and excellent electrical conductivity performance.
[0157] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A composite coating, characterized in that: The composite coating comprises coating I and coating II sequentially deposited on the substrate; The coating I is a plasma polymerized coating formed by plasma of monomer α and monomer β; The monomer α has a structure shown in formula (1-1), wherein Ar is a structure with an aromatic ring, T1 is -OC(O)- or -C(O)-O-, X1 is a connecting part, Y1 is a connecting part, R1, R2 and R3 are independently selected from hydrogen atoms, halogen atoms, C1-C 10 Alkyl or C1-C 10 The halogen atom replaces the alkyl group, The monomer β has a structure shown in formula (2-1), Wherein, S contains one or more -OC(O)- or -C(O)-O-, and R4, R5, R6, R7, R8 and R9 are independently selected from hydrogen atoms, halogen atoms, C1-C 10 Alkyl or C1-C 10 The halogen atom replaces the alkyl group; The coating II is a plasma polymerized coating formed by plasma of monomer γ, wherein the monomer γ has a siloxane having a structure represented by formula (3-1), formula (3-2) or formula (3-3), Among them, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 18 and R 19 are independently selected from hydrogen atoms, C1-C 20 Hydrocarbon or C1-C 20 The alkoxy group, R 17 Selected from C1-C 20 Hydrocarbon, C0-C 20 A hydrocarbon silyl group, n is an integer of 1-100, m is an integer of 3-10, wherein R 10 , R 11 , R 12 and R 13 At least one of R is not a hydrogen atom, 14 , R 15 and R 16 At least one of R is not a hydrogen atom, 18 and R 19 At least one of them is not a hydrogen atom.
2. The composite coating according to claim 1, characterized in that: The R1, R2, R3, R4, R5, R6, R7, R8 and R9 are independently selected from hydrogen atoms or methyl groups.
3. The composite coating according to claim 1, characterized in that: The X1 is a structure shown in the following formula (1-2), *-X 11 -X 12 -* (1-2) Among them, X 11 is a connecting bond, -O- or -C(O)-, X 12 is the connecting key, C1-C 10 Alkylene or C1-C 10 The halogen atom replaces the alkylene group; Y1 is a connecting bond, C1-C 10 Alkylene or C1-C 10 The halogen atom(s) of the alkylene group is substituted by the alkylene group.
4. The composite coating according to claim 1, characterized in that: The Ar is a benzene ring structure or a benzene ring structure with a substituent.
5. The composite coating according to claim 4, characterized in that: The monomer α has a structure shown in formula (1-3), Wherein, T2 is -OC(O)- or -C(O)-O-, X2 is a connecting part, and Y2 is a connecting part; R 21 , R 22 and R 23 are independently selected from hydrogen atoms, halogen atoms, C1-C 10 Alkyl or C1-C 10 The halogen atom replaces the alkyl group.
6. The composite coating according to claim 5, characterized in that: The X2 is a structure shown in the following formula (1-4), *-X 22 -X 21 -* (1-4) Among them, X 21 is a connecting bond, -O- or -C(O)-, X 22 is the connecting key, C1-C 10 Alkylene or C1-C 10 The halogen atom replaces the alkylene group; Y2 is a connecting bond, C1-C 10 Alkylene or C1-C 10 The halogen atom(s) of the alkylene group is substituted by the alkylene group.
7. The composite coating according to claim 5, characterized in that: The R 21 , R 22 and R 23 are independently selected from a hydrogen atom or a methyl group.
8. The composite coating according to claim 1, characterized in that: The monomer α is selected from at least one of 2-phenoxyethyl acrylate, phenyl acrylate, diallyl terephthalate or phenyl methacrylate.
9. The composite coating according to claim 1, characterized in that: The S contains two -OC(O)- or -C(O)-O-.
10. The composite coating according to claim 1, characterized in that: The S has a structure shown in formula (2-2), Among them, R 24 C2-C 10 Alkylene or C2-C 10 The halogen atom-substituted alkylene group is substituted with y, and y is an integer from 0 to 10.
11. The composite coating according to claim 1, characterized in that: The monomer β is selected from at least one of 2-methyl-2-acrylic acid-1,9-nonanediol ester, 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol dimethacrylate, methacrylic anhydride, dipropylene-2-enyl-2-methylenesuccinate, dipropylene-2-enyl 2-benzylidenemalonate, or diethyl diallylmalonate.
12. The composite coating according to claim 1, characterized in that: The R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 18 and R 19 are independently selected from hydrogen, methyl or ethyl, R 17 Selected from methyl, ethyl, silyl, methylsilyl, dimethylsilyl or trimethylsilyl.
13. The composite coating according to claim 1, characterized in that: The monomer γ is selected from one or more of octamethylcyclotetrasiloxane, octamethyltrisiloxane, hexamethylcyclotrisiloxane, trimethylcyclotrisiloxane, tetramethyltetravinylcyclotetrasiloxane, dodecamethylcyclohexasiloxane, decamethylcyclopentasiloxane, decamethyltetrasiloxane, dimethylsiloxane, tetraethoxysilane, tetramethoxysilane, allyltrimethoxysilane, hexamethyldisiloxane, tetramethyldisiloxane, hexaethyldisiloxane, diphenyldimethoxysilane, diphenyldiethoxysilane and phenyltris(trimethylsiloxy)silane.
14. The composite coating according to claim 1, characterized in that: The substrate is metal, plastic, fabric, glass, electrical component, optical instrument or electrical part.
15. The composite coating according to claim 14, characterized in that: The substrate is a PCB board or a data line.
16. The composite coating according to claim 1, characterized in that: The thickness of the coating I is 100-310nm, the thickness of the coating II is 10-50nm, and the thickness of the composite coating is 150-330nm.
17. The composite coating according to claim 1, characterized in that: The coating is electrically conductive.
18. The composite coating according to claim 1, characterized in that: The coating was immersed in artificial sweat with a pH of 4.7, a voltage of 3.7 V was applied, and the circuit current was monitored within 30 minutes. The current change was no greater than 0.6 mA.
19. A method for preparing the composite coating according to any one of claims 1 to 18, characterized in that: include: Providing a substrate, placing the substrate in a plasma reaction chamber, evacuating the chamber to 10-200 mTorr, and introducing an inert gas such as He, Ar, O2 or a mixed gas thereof; The vapor of monomer α and monomer β is introduced into the reaction chamber, and plasma discharge is started to form a plasma polymerization coating I; The steam of monomer γ is introduced into the reaction chamber, and plasma discharge is started to form a plasma polymerized coating II on the surface of the coating I.
20. The preparation method according to claim 19, characterized in that: The thickness of coating I and / or coating II is adjusted to ensure that the coating has acid sweat protection and electrical conductivity.
21. A device, characterized in that At least part of the surface of the device has the composite coating according to any one of claims 1 to 18.
Citation Information
Patent Citations
Composite coating, preparation method and device
CN113025096A
Battery with coating and preparation method thereof
CN115411420A
Protective coating
US20190344307A1